Tau Oligomers: Cytotoxicity, Propagation, and Mitochondrial Damage - Shafiei, Scott S.; Guerrero-Muñoz, Marcos J.; Castillo-Carranza, Diana L. (Frontiers in Aging Neuroscience, 2017)
Aging has long been considered as the main risk factor for several neurodegenerative disorders including a large group of diseases known as tauopathies. Even though neurofibrillary tangles (NFTs) have been examined as the main histopathological hallmark, they do not seem to play a role as the toxic entities leading to disease. Recent studies suggest that an intermediate form of tau, prior to NFT formation, the tau oligomer, is the true toxic species. However, the mechanisms by which tau oligomers trigger neurodegeneration remain unknown. This review summarizes recent findings regarding the role of tau oligomers in disease, including release from cells, propagation from affected to unaffected brain regions, uptake into cells, and toxicity via mitochondrial dysfunction. A greater understanding of tauopathies may lead to future advancements in regards to prevention and treatment.